Strategi kolaborasi TNI Angkatan Laut dalam penanganan Limbah Nuklir Pasca Konflik Perang untuk Keamanan Lingkungan Maritim di Laut Natuna Utara - Rahadian Nur Bramantyo; Buddy Suseto; Karadona Karadona (EduInovasi: Journal of Basic Educational Studies, 2025)
The collaborative role of the Indonesian Navy (TNI AL) is very important in addressing the potential risk of nuclear waste in the strategic area of North Natuna, which is passed by international shipping routes. This study was compiled using a qualitative descriptive approach through a literature review technique, by analyzing national regulations, defense documents, and technical regulations from institutions such as BAPETEN, BRIN, and KLHK. The results of the study indicate that the TNI AL has the potential for a legal basis through Military Operations Other Than War (OMSP), but active involvement in nuclear waste management is not yet clearly stated in the technical regulations regarding nuclear power. Structural problems such as overlapping authority, lack of mitigation and identification infrastructure, and the lack of integration of regulations between ministerial and institutional sectors also hinder the effectiveness of this role. Increasing the role of the TNI AL in the surveillance and response system for the maritime environment requires policy harmonization and strengthening collaboration between agencies as an important part of the national maritime security system.